Phenotypic Markers Reflecting the Status of Overstressed Tea Plants Subjected to Repeated Shade Cultivation - Yamashita, Hiroto; Tanaka, Yasuno; Umetsu, Keisuke; Morita, Sakurako; Ono, Yoshiki; Suzuki, Toshikazu; Takemoto, Tetsuyuki; Morita, Akio; Ikka, Takashi (Frontiers in Plant Science, 2020)
Shade cultivation is a traditional Japanese tea cultivation method in which the shoot buds are shaded for several weeks. This technique is increasingly used for green tea production because it produces tea of high quality (as indicated by umami and nutritional content) and commands high prices. However, given that shaded tea plants are grown under low-light stress, concerns exist regarding damage to tea plants caused by repeated shade cultivation. To understand basic physiological responses and accumulative changes in photosynthetic ability and metabolites of tea plants subjected to repeated shading, we performed a pot experiment on immature tea plants grown in a growth chamber subjected to repeated shading treatments. The results demonstrated that shade cultivation caused a decrease in non-structural carbohydrate content and an increase of several degrees in leaf surface temperature, reflecting transpiration through the leaf stomata, as a result of a reduction in photosynthetic ability. An increase of several degrees in canopy temperature and a reduction in photosynthetic ability in the field in the mid-summer season was also observed in overstressed tea plants subjected to repeated shading. Metabolomic analysis identified several candidate biomarkers, such as citrulline and glycine betaine, that were significantly changed in individuals affected by shade cultivation. These physiological changes may be an indicator of the stress status of tea plants grown under repeated shade cultivation.